The pro-apoptotic and cytotoxic efficacy of polydatin encapsulated poly(lactic-co-glycolic acid) (PLGA) nanoparticles. (December 2021) - Vijayalakshmi, Sankaran; Rajasekar, Aruliah; Veeraraghavan, Vishnu Priya; Ghidan, Alaa Yousef; M. Al Antary, Tawfiq; Karthikkumar, Venkatachalam; Damodaran, Lakshmi Priya Malarveni; Vinayagam, Ramachandran; David, Ernest
Graphical abstract: Highlights: Polydatin (POL) loaded-PLGA into the synthesized NPs against KB cells. A better anti-apoptosis effect has been achieved by POL-PLGA-NPs. POL-PLGA-NPs may serve anticancer activities against KB cancer cells. POL-PLGA NPs displayed promising antioxidant activity. Abstract: Polydatin (POL) is an ingredient of many herbal medications and has pharmacological properties. The present study aimed to determine the antitumor potential of Polydatin loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (POL-PLGA-NPs) against the cancerous KB cell line. We evaluated the efficiency of synthesized nanoparticles on cell proliferation and apoptosis markers, in addition to the generation of reactive oxygen species (ROS) and its potential to induce damages on the mitochondrial membrane. Morphological changes in the cells (damage to DNA incurred due to cell lysis) were observed under Ethidium Bromide and Acridine orange staining techniques. The results evidenced the loss of cell viability, increased ROS, altered lipid peroxidation levels, increased DNA damage and loss of mitochondrial membrane potential in target cancerous KB cells. Further, immunoblot analysis quantified the expression of caspases-3, -9 and poly(ADP-ribose) polymerase (PARP) also supports the cell damage. Thus, the findings of the study suggested that POL-PLGA-NPs effectively induced oxidative stress by initiating cellular damage leading to apoptosis in KB cells.